Penerapan Model Arima Dalam Rangka Forecasting Pengunjung Nasabah Prioritas Dan Non-Prioritas Bank Mandiri Di Executive Lounge Blue Sky, Bandara Soekarno Hatta - Vera Sylvia Saragi Sitio (Journal of Economics and Business Aseanomics (JEBA), 2018)
Increasing number of use air transportation in communities, encourage Soekarno Hatta airport as the biggest International Airport in Indonesia to increase service facilities one of which is providing executive lounge and partnership with other company. The aim of this research are to know the pattern data of priority and non- priority Mandiri Bank, the bestforecasting model and forecasting number of visitors for two years. Metod of this research is descriptive with quantitative model namely ARIMA model (Autoregressive Integrated Moving Average) Box and Jenkis with using minitab 18 software. Secondary data is using from number of visitors on September 2015 â€“ September 2016. The result of this research showed that data pattern is seasonal data of both data (priority and on-priority Mandiri Bank). The model ARIMA for priority ias ARIMA (1,1,0) and non priority is (3,0,2). The result of forecasting showed that number of visitors will increase every months for two year butÂ  it was not significant. Expecialy, non-priority Mandiri Bank have significant increase in Eid Al-Fitr, Christmas Eve and School Holiday.